Unilateral diplopia and ptosis in a child with COVID-19 revealing third cranial nerve palsy. Issue 9 (September 2021) - Elenga, Narcisse; Martin, Elise; Gerard, Max; Osei, Lindsay; Rasouly, Najibullah
Abstract: We report the case of a 10-year-old boy with acute–onset diplopia and ptosis in the right eye. CR was positive for SARS-CoV-2. The patient was managed successfully with corticosteroids. We highlight the need for heightened suspicion of occult COVID-19 infection among children presenting with unusual III nerve palsy.